Adapting the Everyday Discrimination Scale to Medical Settings: Reliability and Validity Testing in a Sample of African American Patients - Peek, Monica E. (2011)
OBJECTIVE: Despite evidence that discrimination within the health care system may play an important role in perpetuating health disparities, instruments designed to measure discrimination within the health care setting have not been adequately tested or validated. Consequently, we sought to test the psychometric properties of a modified version of the Everyday Discrimination scale, adapted for medical settings. DESIGN: Cross-sectional study. SETTING: Academic medical center in Chicago. PARTICIPANTS: Seventy-four African American patients. OUTCOME MEASURES: We measured factor analysis, internal consistency, test-retest reliability, convergent validity and discriminant validity. RESULTS: Seventy-four participants completed the baseline interviews and 66 participants (89%) completed the follow-up interviews. Eighty percent were women. The Discrimination in Medical Settings (DMS) Scale had a single factor solution (eigenvalue of 4.36), a Cronbach’s alpha of 0.89 and test-retest reliability of .58 (P<.0001). The DMS was significantly correlated with an overall measure of societal discrimination (EOD) (r=.51, P<.001) as well as two of its three subscales (unfair: r=−.04, P=.76; discrimination: r=.45, P<0.001; worry: r=−.36, P=.002). The DMS was associated with the overall African American Trust in Health Care Scale (r=.27, P=.02) as well as two key subscales (racism: r=.31, P<.001; disrespect: r=.44, P<.001). The DMS scale was inversely associated with the Social Desirability Scale (r=.18, P=.13). The DMS scale was not correlated with the Center for Epidemiologic Studies Depression Scale (r=.03, P=.80). CONCLUSIONS: The Discrimination in Medical Settings Scale has excellent internal consistency, test-retest reliability, convergent validity and discriminant validity among our sample of African American patients. Further testing is warranted among other racial/ethnic groups.